Increased recruitment of cognitive control in the presence of traumatic stimuli in complex PTSD - Herzog, Julia; Niedtfeld, Inga; Rausch, Sophie; Thome, Janine; Bohus, Martin; Schmahl, Christian (European archives of psychiatry and clinical neuroscience, 2017)
A neurocircuitry model of post-traumatic stress disorder (PTSD) suggests increased amygdala responses to emotional stimuli, coupled with hypoactivation of prefrontal regions associated with cognitive control. However, results are heterogenous across different subsamples of PTSD as well as different paradigms. We investigated cognitive control in a classic and emotional Stroop task in 28 female patients with complex PTSD (cPTSD), 28 female trauma-exposed healthy controls (TCs) and 28 female non-trauma-exposed healthy controls (HCs) using functional neuroimaging. Afterwards, we assessed memory function in a spontaneous free recall and recognition task. Patients with cPTSD displayed significantly greater Stroop interference with trauma-related words (as reflected in slower reaction times and increased errors) compared to the other conditions and compared to the TC and HC groups. Moreover, patients with cPTSD showed increased activation in the context of trauma-related words in brain regions associated with cognitive control (dlPFC, vmPFC, dACC) compared to both control groups, and a trend for increased activation in the insula compared to the HC group. Increased recruitment of regions contributing to cognitive control in patients with cPTSD, together with a lack of amygdala response may point to efforts to compensate for emotional distraction caused by the trauma-related words.